Exploring the Trends of Retail formats in India:A Study of Hypermarkets in Bangalore City - Jahan, Noor Firdoos; Ramakrishnan, Lalitha (Indian Journal of Marketing, 2009)
The Indian retail industry is one of the fastest growing industries with an annual growth of 30%. It is transforming into a big corporate multinational business with a potential to create direct employment opportunities of 2.5 million jobs and 10 million additional jobs in support activities. The formats are undergoing a change from convenience store to hyper markets with the entry of leading corporate in India like TATA, Reliance, Birla, and Pantaloon India pvt. Ltd., and top foreign retailers like Wal-Mart and others. Today the country has around 40 hypermarkets, but the estimates shows that India's 67-odd retail destinations can easily accommodate over 1,000 hypermarkets by 2010. This paper presents the results of this empirical study conducted at Bangalore city. A sample of 265 customers of hypermarkets was randomly selected for this study.